Numerical Study of Excavation In Soil Clay Support by Piles with Anchors - فياض, توفيق (Latakia University Journal -Engineering Sciences Series, 2020)
Walls piles supported with Anchors are considered one of most ways of engineering supporting widespread. This research includes studying the behaviorof walls pile, through a numerical parametric study using the (plaxis / 2D) program. the study includes the most influencing factors which include:(the angle of the inclination, the vertical spacing between the rows of Anchors andthe distance of the first row of anchors from the ground surface). The effect of these factors on the stability of the wall was studied.Where they give the best effectto the anchors and ensure the best possible positioning which contributes to reducing the economic cost of this constructions.